2020
DOI: 10.26480/wcm.01.2020.20.31
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change Vulnerability and Responses of Fisherfolk Communities in the South-Eastern Coast of Bangladesh

Abstract: Climate change is an ongoing threat across the earth–especially those who depend on fishing. This study aims to understand how fishery-dependent communities in the South-Eastern coast of Bangladesh build resilience against environmental stresses, and in what ways their strategies sometimes fail. A composite index approach has been used to calculate livelihood vulnerability. Results reveal that exposure to floods and cyclones, sensitivity and lack of adaptive capacity concerning physical, natural, and financial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 0 publications
0
28
0
Order By: Relevance
“…Livelihood of the fishermen impacted by numbers of climate induced hazards like cyclones, floods and rising sea levels and their fishing actions are affected mainly due to cyclones. Barua et al (2020) found the lessening of the days of fishing by fishermen in Bangladesh significantly MSCRA increased due to cyclones, depression and larger vacillation in the production of marine and coastal fisheries because of the present scenario of changing climate and climate variability. These impacts, taken jointly, may additionally augment the vulnerability of sustainable livelihood for the coastal fisherfolks devoid of adaptation practices in response of the changing climate.…”
Section: Management Of Agriculture Products Value Chainmentioning
confidence: 99%
See 3 more Smart Citations
“…Livelihood of the fishermen impacted by numbers of climate induced hazards like cyclones, floods and rising sea levels and their fishing actions are affected mainly due to cyclones. Barua et al (2020) found the lessening of the days of fishing by fishermen in Bangladesh significantly MSCRA increased due to cyclones, depression and larger vacillation in the production of marine and coastal fisheries because of the present scenario of changing climate and climate variability. These impacts, taken jointly, may additionally augment the vulnerability of sustainable livelihood for the coastal fisherfolks devoid of adaptation practices in response of the changing climate.…”
Section: Management Of Agriculture Products Value Chainmentioning
confidence: 99%
“…Livelihood of the fishermen impacted by numbers of climate induced hazards like cyclones, floods and rising sea levels and their fishing actions are affected mainly due to cyclones. Barua et al (2020) found the lessening of the days of fishing by fishermen in Bangladesh significantly…”
Section: Management Of Agriculture Products Value Chainmentioning
confidence: 99%
See 2 more Smart Citations
“…Many societies depend on coastal productivity, which can sum up to 15% of the animal protein and support 10–12% of the global population (Barua et al 2020). The fishery is vital for the economy of developing countries, which, together, contribute to 54% of global fishery exportation (FAO 2018), and where most of the people who depend on this activity—and who also deal with low incoming and limited food resources—live.…”
mentioning
confidence: 99%